Editorial - Sánchez Gamboa, Silvio Ancisar (Universidade Estadual de Campinas, 2020)
Editorial of V.11, n. 3 (2019). It guides readers on the structure and organization of the edition and presents the main contents of the publication, as well as a brief assessment of the participation of the reviewers in the three numbers of volume 11 corresponding to 2019.